2011
DOI: 10.1558/ijsll.v18i2.293
|View full text |Cite
|
Sign up to set email alerts
|

International Practices in Forensic Speaker Comparison

Abstract: The results of the first international survey on forensic speaker comparison practices are presented in this paper. Thirty-six experts from 13 countries and 5 continents responded to a series of questions concerning their practices in casework. Despite the responses revealing a range of differences, there is nevertheless a reasonably strong convergence with respect to the importance assigned to particular speech features, methodology and choice of framework for expressing conclusions. Practices and preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 0 publications
0
70
0
13
Order By: Relevance
“…En la comparación forense de voces, la mayoría de expertos y laboratorios utilizan una combinación de análisis lingüístico y acústico (Gold & French, 2011), complementado en ocasiones con herramientas automáticas (Delgado, 2005;González & Lucena, 2005, para citar a investigadores españoles) basadas en el marco bayesiano. La elección de una metodología u otra depende no solo de los medios disponibles, sino también de la pregunta de investigación objeto del análisis.…”
Section: Objetivos E Hipótesisunclassified
“…En la comparación forense de voces, la mayoría de expertos y laboratorios utilizan una combinación de análisis lingüístico y acústico (Gold & French, 2011), complementado en ocasiones con herramientas automáticas (Delgado, 2005;González & Lucena, 2005, para citar a investigadores españoles) basadas en el marco bayesiano. La elección de una metodología u otra depende no solo de los medios disponibles, sino también de la pregunta de investigación objeto del análisis.…”
Section: Objetivos E Hipótesisunclassified
“…These experts are often phoneticians who have obtained additional training in forensic science, or engineers or computer scientists who have obtained additional training in phonetics and forensic science [14]. World-wide surveys on forensic speech investigation [15,16] show that the most popular approach employed in most countries are auditory analysis, together with acoustic-phonetic analysis. Reich [4] conducted an experiment where two groups of listeners, naive (undergraduate students) and sophisticated (doctoral students and professors in speech and hearing sciences), discriminated disguised and undisguised speech created by forty male speakers.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted by Reference [3] with thirty-six professionals on forensic speaker comparison revealed that the main suprasegmental phonetic information to be measured was the fundamental frequency and its statistical descriptors (mean, median, standard deviation, range, and others). Nevertheless, the experts emphasized that those aspects are used as an elimination tool rather than an identification tool.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the experts emphasized that those aspects are used as an elimination tool rather than an identification tool. Reference [3] also pointed out that all experts analyze segmental features as formant frequencies and consonant-vowel transitions, among others.…”
Section: Introductionmentioning
confidence: 99%